Mobile Educational Application on Learning Electric Circuit for Primary School Using Augmented Reality - Ang, Yong Yi; Senan, Norhalina (Applied Information Technology And Computer Science, 2023)
Electric circuits is one of the topics in Science which is being taught in year 2 primary school. However, most of the primary school lack of availability of laboratory and equipments for student to conduct experiments. The existing applications to learn electric circuit on Google Play are commonly not implemented with Augmented Reality (AR) and lack of learning module. Hence, mobile educational application on learning electric circuit using marker-based AR technology is developed on the Android platform to help user to explore the knowledge of electric circuit through an immersive environment. The user acceptance test has been conducted among 30 target users from SK Parit Raja. Positive results were obtained with an average of 69.13% strongly agreed and 28.54% agreed with the functionality and usefulness of the application. In conclusion, this application is appropriate for use as a teaching tool and learning medium for students to learn about electrical circuits.